Quality Control of Glehniae Radix, the Root of Glehnia Littoralis Fr. Schmidt ex Miq., Along its Value Chains - Chen, Yuan; Lei, Lujing; Bi, Yaqiong; Jiang, Linlin; Guo, Wenfang; Wang, Jianhua; Li, Minhui (Frontiers in Pharmacology, 2021)
Glehniae Radix (GR) is one of the major medicinal materials in China. The global demand for GR, especially in Asian countries, is constantly increasing, and the supply of wild medicinal materials falls short of the demand. Artificial planting is an important method to solve the shortage of medicinal materials. Previous studies have shown that the production and processing modes of different value chains (VCs) have an impact on the quality of medicinal materials. After four years of field and market research, this paper interviews stakeholders in the VCs, integrates different types of VCs and further analyzes the VCs. And the polysaccharide content of the collected samples from different producing areas, the xanthotoxin (XAT), heavy metal content, and pesticide residues were determined, and the effective components were further analyzed by the K-means clustering method. At the same time, the local price and market price of GR in Chifeng, Inner Mongolia, and Anguo, Hebei were collected, and the ARIMA (Autoregressive Integrated Moving Average) method was used to predict the price. Ten VCs are summarized in this article. It is concluded that the income of the staff at the beginning of the chain is not high. According to the analysis of chemical composition and clustering results, the quality of the medicinal materials in Chifeng is better than that in other study areas, so the price of the medicinal materials is relatively high, which echoes the market price. The prediction results of the price can provide a reference for the choice of planting medicinal materials in the future. Through the study, it was found that the vertical integration in the VCs of GR could not only guarantee the benefit of the growers but also guarantee the traceability of the medicinal materials, to further guarantee the quality of the medicinal materials. The complex relationship between the cultivation area and the quality of the medicinal materials is not clear, which should be paid more attention to in future research.